Cover Picture: Bidentate Chiral Bis(imidazolium)‐Based Halogen‐Bond Donors: Synthesis and Applications in Enantioselective Recognition and Catalysis (Angew. Chem. Int. Ed. 17/2020). Issue 17 (25th March 2020) - Sutar, Revannath L.; Engelage, Elric; Stoll, Raphael; Huber, Stefan M.
Abstract : Halogen bonding is by now established in noncovalent organocatalysis, but enantioselective applications are still very rare. In their Communication on page 6806, S. M. Huber et al. show that chiral bidentate halogen bond donors are able to differentiate the enantiomers of a diamine via NMR spectroscopy and that they can also be used to induce moderate enantioselectivity in a Mukaiyama aldol reaction. This is the first case in which enantioinduction was achieved with a "pure" halogen bond donor.